Bound constrained smooth optimization for solving variational inequalities and related problems - Andreani, Roberto [UNESP]; Friedlander, Ana (Springer Nature, 2002)
Variational inequalities and related problems may be solved via smooth bound constrained optimization. A comprehensive discussion of the important features involved with this strategy is presented. Complementarity problems and mathematical programming problems with equilibrium constraints are included in this report. Numerical experiments are commented. Conclusions and directions of future research are indicated.
Keywords: Bound constrained optimization; Merit functions; Variational inequalities